2011
DOI: 10.1097/fjc.0b013e318220e37f
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous κ-Opioid Peptide Mediates the Cardioprotection Induced by Ischemic Postconditioning

Abstract: The aim of this study was to investigate the underlying mechanism that dynorphin, an endogenous kappa opioid receptor (κ-OR) agonist, triggers antiapoptotic effect of postconditioning (Postcon). In addition to vehicle treatment, Sprague Dawley rats (n = 6) underwent a 30-minute left anterior descending occlusion followed by 2 hours of reperfusion with or without a Postcon stimulus. The selective κ-OR antagonist nor-binaltorphimine (Nor-BNI) was administered intravenously 5 minutes before reperfusion. Infarct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Nor-BNI was used at a dose 9 mg/kg as recommended by Birch et al (1987), and several recent reports demonstrated that even lower doses (0.3-2.0 mg/kg) of this antagonist inhibited κ-OR-mediated effects (Gross et al, 2010;Guo et al, 2011;Tong et al, 2011;LonghiBalbinot et al, 2011). BNTX at a dose of 0.7 mg/kg eliminated neither the infarct-sparing effect (Maslov et al, 2009) nor the antinociceptive effect of the selective δ 2 -OR agonist deltorphin II (Sofuoglu et al, 1993), but it increased the antinociceptive ED 50 value of the intrathecally administered δ 1 -OR agonist DPDPE 5.9-fold (Sofuoglu et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Nor-BNI was used at a dose 9 mg/kg as recommended by Birch et al (1987), and several recent reports demonstrated that even lower doses (0.3-2.0 mg/kg) of this antagonist inhibited κ-OR-mediated effects (Gross et al, 2010;Guo et al, 2011;Tong et al, 2011;LonghiBalbinot et al, 2011). BNTX at a dose of 0.7 mg/kg eliminated neither the infarct-sparing effect (Maslov et al, 2009) nor the antinociceptive effect of the selective δ 2 -OR agonist deltorphin II (Sofuoglu et al, 1993), but it increased the antinociceptive ED 50 value of the intrathecally administered δ 1 -OR agonist DPDPE 5.9-fold (Sofuoglu et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to studies implicating DOR and possibly MOR involvement, Guo et al . () report increased cardiac content of the KOR peptide dynorphin during ischaemic post‐conditioning in rats, in association with KOR‐antagonist sensitive protection.…”
Section: The Endogenous Opioid Receptor System Underpins Ischaemic Prmentioning
confidence: 95%
“…The most important receptor for protection is the δ receptor. A specific δ receptor antagonist reduces cardioprotection markedly, whereas a κ receptor antagonist has little effects on ischaemic preconditioning (Schultz et al ., ; Aitchison et al ., ) and ischaemic postconditioning in rats (Jang et al ., ; Zatta et al ., ; Guo et al ., ), and during RIPC in rats (Wong et al ., ).…”
Section: Extracellular Receptor Ligands In Conditioningmentioning
confidence: 99%